Changes in volumetric bone mineral density after ACL reconstruction with single-bundle and double-bundle: a 1-year follow-up study using peripheral quantitative computed tomography - Yin, Binbin; Fang, Chaohua; Feng, Ren hai; Wu, Jian min (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundThe purpose of this study is to quantify changes in volumetric bone mineral density (vBMD) in different regions of the tibial plateau after single-bundle (SB) and double-bundle (DB) anterior cruciate ligament reconstruction (ACLR).MethodsTwenty-six patients with diagnosed anterior cruciate ligament (ACL) rupture were allocated into SB (10) or DB group (16) and completed the last follow-up at 12 months. Peripheral quantitative computed tomography (pQCT) was performed before surgery and at 1, 3, 6, and 12 months after surgery. Four regions of interest (ROI) were identified 2 mm below the medial and lateral subchondral plate of the knee joint, namely, the anteromedial (AM), posteromedial (PM), anterolateral (AL) and posterolateral (PL) regions. The vBMD of each ROI was measured and compared between the groups at different timepoints.ResultsFor the vBMD, a significant change in all ROIs can be found over time, with the values at all ROIs decreased until 6 months postoperatively and then steadily increased, but the values did not reach preoperative levels. The AM region had the highest vBMD, followed by the PL region, and the vBMD was lowest in the AL region. For the change percent, the decrease magnitude was comparable between AM and PM region at postoperative 1 and 12 months, but it was greater at PM region at postoperative 3 and 6 months. Comparing DB ACLR and SB ACLR, there was no significant difference in the change percent of vBMD in all ROIs, except for in the AL region at 1 month postoperatively.ConclusionA partially reversible decline in vBMD was found in the proximal tibia at 12 months after ACLR. But the change percent varied among the different regions, which may indicate inadequate restoration of knee kinematics after ACLR. DB and SB ACLR methods may have a similar effect on knee kinematics.